NAVIGATING THE NEW NORMS: AN HR LEADER'S GUIDE TO DEI, WELL-BEING, AND FLEXIBLE WORK - Ari Fitriany; Oktavianti; Rizki Eka Putra (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The contemporary workplace is undergoing a fundamental transformation, driven by post-pandemic expectations, social justice movements, and a heightened focus on holistic employee value. This research investigates the complex interplay between Diversity, Equity, and Inclusion (DEI), employee well-being, and flexible work models as the three pillars of the "new norms" in people management. Employing a multi-case study methodology, the study analyzed the integrated strategies of five purpose-driven organizations over an 18-month period. Results indicate that a siloed approach to these domains leads to initiative fatigue and diminished impact. Successful organizations demonstrated that authentic, data-driven DEI efforts create psychological safety, which underpins well-being. Furthermore, structured flexibility, when managed with clear principles of equity and accountability, was found to enhance both inclusion and mental health outcomes. The discussion argues that HR leaders must transition from programmatic thinking to systemic integration, where policies in one domain actively reinforce the others. The study concludes by providing a practical framework for navigating these interconnected priorities to build resilient, adaptive, and high-performing organizations.